Influence of soil type on bacterial growth and tolerance to experimentally added human antibiotics - Laura Rodríguez-González; Montserrat Díaz-Raviña; Beatriz Sevilla-Morán; Elena García-Campos; Juan José Villaverde; Manuel Arias-Estévez; David Fernández-Calviño; Vanesa Santás-Miguel (Ecotoxicology and Environmental Safety)
The human antibiotics cefuroxime (CXM) and azithromycin (AZI) are among the most commonly prescribed. A significant portion of both are excreted and has been detected in sewage treatment plant effluents. The increasing use of such effluents in crops for irrigation and as fertilisers poses a threat to soil microbiota because of the presence of antibiotics. The lack of studies on CXM and AZI in soils hinders our understanding of their potential toxic effects on soil bacterial communities and ecosystem services. This study significantly contributes to the literature by quantifying the toxicity of CXM and AZI at varying concentrations in 12 different crop soils and tracking their evolution over time. The study also examined whether antibiotic pressure led to the development of more tolerant bacterial communities. The results of this study are the values of the logarithm of the antibiotic concentration at which 50 % of bacterial growth is inhibited (Log IC50) and indicate that both antibiotics are toxic to soil bacteria. The direct toxicity of CXM (1 day after contamination) was higher (Log IC50: 0.9 = 7.9 mg kg−1) than that of AZI (Log IC50: 3.4 = 2362 mg kg−1). However, bacterial growth was less affected by CXM over time, whereas AZI remained toxic in some soils until day 42 (Log IC50: 3.2 = 1533 mg kg−1 and 3.4 = 2291 mg kg−1, respectively). The overall results indicate that selective pressure exerted by antibiotics generates antibiotic tolerance in soils, even at the lowest antibiotic concentration studied (7.8 mg kg−1). The general trend was to increase tolerance to higher antibiotic concentrations up to the highest concentration studied (2000 mg kg−1). However, the degree of tolerance developed was highly dependent on soil type. More studies should be conducted to quantitatively assess the toxic and tolerance-developing effects of antibiotics in soils. Such information will be valuable for identifying which antibiotics pose a threat to the soil microbiota and consequently to human health.